Global Perspectives on the United States : Pro-Americanism, Anti-Americanism, and the Discourses Between - Desmond, Jane; Domínguez, Virginia R. (Book collections on Project MUSE., 2017)
"This edited collection emphasizes public discourse and the related circulation of debates, practices, and commodities that get perceived abroad as having an American origin, such as hip-hop in Japan or the organization of higher education in Germany. These essays provide a unique, global perspective on America, because they are authored by Americanist scholars situated outside of the United States, and working in Britain, Japan, Germany, Kazakhstan, Egypt, South Africa, Panama, Mexico, the Republic of Georgia, Hungary, Norway, and Poland. Encompassing a range of disciplines, including literary studies, art history, political science, and sociology, the collection aims to provide a series of in-depth case studies that focus on specific cultural practices, as well as the importation and exportation of institutional organizational systems. Rather than simply accepting as its starting point the idea of 'Pro-Americanism' and 'Anti-Americanism, ' this project analyzes the production of those concepts when attached to specific social practices, and uncovers the impact that such labeling has on social change within the specific cultural and political contexts of disparate locations. The collection emerges out of research done by the International Forum for U.S. Studies scholars, and includes essays that cover a range of topics, such as the Arab uprising in Egypt, 9/11, U.S.-Latin American relations, and global responses to the Civil Rights Movement"--